Serum protein concentrations of cattle withnatural fasciola hepatica and strongylids infections - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Thomazini, Camila Martos [UNESP]; Moraes, Lívia Fagundes [UNESP]; Dias, Rafael Grobério Souto [UNESP]; Reis, Rafael de Oliveira [UNESP]; Takahira, Regina Kiomi [UNESP]; Lopes, Raimundo Souza [UNESP]; Fagliari, José Jurandir [UNESP]; Silva, Paulo César da [UNESP] (Wiley, 2011)
Acute phase proteins (APPs) are considered sensitive markers ofinflammation especially in large animals. In this study we deter-mined the profile of acute phase proteins in parasitic diseases using22 Nellore cattle. They were naturally infected with Fasciola hepat-ica and strongylids, which included 70% Cooperia sp., 22%Oesophagostomum sp., 7% Haemonchus sp. and 1% Trichostrongylus sp. by egg count per gram and coprocultures. Serum concentra-tions of acute phase proteins were determined by means of sodiumdodecyl sulphate-polycrylamide gel electrophoresis. Increaseswere observed in concentrations of IgG 4,083  1,034 mg/dL(maximum of 6,765 mg/dL), ceruloplasmin 78.9  22.7 mg/dL(maximum of 119.7 mg/dL – 10 times fold), transferrin 361 114.4 mg/dL, haptoglobin 22.8  14.8 mg/dL (maximum of66.7 mg/dL – 3 times fold), and a1-acid glycoprotein 11.3 5.7 mg/dL (maximum of 24.1 – 2 times fold). The liver enzymesAST and GGT were also increased at 132.2  33 UI/L (maximum of199.5 UI/L) and 282.8  156.6 UI/L (maximum of 650 UI/L). Se-rum total protein, IgA, albumin, and non-nominal identified pro-tein of 23 kD were not significantly increased (P 4 0.05). Theincreases in serum AST, GGT, and the acute phase proteins (cer-uloplasmin, haptoglobin, a1-acid glycoprotein, and specially IgG)demonstrate acute hepatic inflammation mainly caused by Fasciolahepatica. Otherwise, the other parasites may also contribute to thechanges in the acute phase protein concentrations.